2013
DOI: 10.1063/1.4807125
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic integration of light-emitting diodes and power metal-oxide-semiconductor channel high-electron-mobility transistors for light-emitting power integrated circuits in GaN on sapphire substrate

Abstract: We report the demonstration of monolithically integrated light-emitting diodes (LEDs) and power metal-oxide-semiconductor channel high-electron-mobility transistors (HEMTs) in GaN. The structure comprised a direct epitaxial integration of layers typical for a GaN-based LED grown directly on top of the layers of a GaN-based HEMT. The layers were then fabricated into a serially connected pair of GaN LED and metal-oxide-semiconductor-gated 0.3 lm-channel HEMT by exposing the LED/HEMT epitaxial layers in selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 10 publications
2
68
0
Order By: Relevance
“…In 2013, the Li [4] of Rensselaer Polytechnic Institute proposed one of the basic and typical designs of LED based HEMT. The device is a monolithic integrated transistor based on the high electron mobility of light-emitting diodes and power metal oxide semiconductor channels.…”
Section: Reviews Of Design and Fabrication Of Homogeneous Structuresmentioning
confidence: 99%
“…In 2013, the Li [4] of Rensselaer Polytechnic Institute proposed one of the basic and typical designs of LED based HEMT. The device is a monolithic integrated transistor based on the high electron mobility of light-emitting diodes and power metal oxide semiconductor channels.…”
Section: Reviews Of Design and Fabrication Of Homogeneous Structuresmentioning
confidence: 99%
“…Furthermore, monolithic integration of III-nitride HEMTs and LEDs on a common platform can effectively reduce undesirable parasitics, thereby enhancing the power efficiency of the driving circuits. To date, Li et al [2] have reported the growth of GaN-based LEDs on HEMTs, and selective removal of the LED-epi was performed for device integration. However, the LED performance was much inferior to that of discrete devices, probably due to the use of an un-optimized growth scheme on HEMTs.…”
Section: Introductionmentioning
confidence: 99%
“…There are attempts to grow the pn‐junction light‐emitting diode (LED) and heterojunction HEMT structures on a same wafer . The main purpose of this integration scheme is to provide on‐chip electrical control of the LED for compact lighting systems.…”
Section: Introductionmentioning
confidence: 99%